Exhaled breath hydrogen cyanide as a marker of early Pseudomonas aeruginosa infection in children with cystic fibrosis - Gilchrist, Francis J.; Belcher, John; Jones, Andrew M.; Smith, David; Smyth, Alan R.; Southern, Kevin W.; Španěl, Patrik; Webb, A. Kevin; Lenney, Warren (European Respiratory Society, 2015)
Hydrogen cyanide is readily detected in the headspace above Pseudomonas aeruginosa cultures and in the breath of cystic fibrosis (CF) patients with chronic (P. aeruginosa) infection. We investigated if exhaled breath HCN is an early marker of P. aeruginosa infection.